СИСТЕМИ ПЕРЕДАЧІ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ ПОСТІЙНИМ СТРУМОМ. ДИНАМІЧНА МОДЕЛЬ ПЕРЕТВОРЮВАЧА З ЛІНІЙНОЮ КОМУТАЦІЄЮ - Павловський, В.В.; Приходько, А.В. (Інститут електродинаміки Національної академії наук України, 2020)
A brief overview of HVDC transmission systems and the main issues that can be resolved with HVDC systems were described in this article. A comparison between two technologies HVDC systems - Line Commutated Converter (LCC) and Voltage Source Converter (VSC) was presented. Load flow and RMS simulation were calculated with the software DIgSILENT PowerFactory to evaluate the behavior of the model and to analyze the main characteristics of the HVDC system model with line commutated converter. References  11, figures 4, table.